Nature of magnetism in Ca 3Co 2O 6 - Wu, Hua; Haverkort, Maurits W. (Physical review letters, 2005)
We find using local spin density approximation+Hubbard U band structure calculations that the novel one-dimensional cobaltate Ca3Co2O6 is not a ferromagnetic half-metal but a Mott insulator. Both the octahedral and the trigonal Co ions are formally trivalent, with the octahedral being in the low-spin and the trigonal in the high-spin state. The inclusion of the spin-orbit coupling leads to the occupation of the minority-spin d2 orbital for the unusually coordinated trigonal Co, producing a giant orbital moment (1.57μB). It also results in an anomalously large magnetocrystalline anisotropy (of order 70 meV), elucidating why the magnetism is highly Ising-like. The role of the oxygen holes, carrying an induced magnetic moment of 0.13μB per oxygen, for the exchange interactions is discussed.